Как загасить звезду: роман / Ольга Играева - Играева Ольга (Серия "Русский бестселлер", 2003)
Экземпляры: (20190205) / Инвентарный номер: 40557 / Цена: 53.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: И 27 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6